Antioxidant effect of yeast on lipid oxidation in salami sausage - Liu, Yingli; Cao, Yating; Yohannes Woldemariam, Kalekristos; Zhong, Shengjie; Yu, Qinglin; Wang, Jing (Frontiers in Microbiology, 2023)
Salami is a kind of fermented meat product with rich nutrition and unique flavor. Because it is rich in fat, it is easy to oxidize to produce bad flavor. Compared with the way of adding artificial or natural antioxidants to reduce the degree of sausage oxidation, the antioxidant characteristics of developing the starter itself deserve more attention. In this study, firstly the antioxidant activities of 5 strains of yeast were measured in vitro, and the results showed that Wickerhamomyces anomalus Y12-3 and Y12-4 had strong tolerance to H2O2 and higher SOD and CAT enzyme activities. While considering the great difference between sausage system and in vitro test environment, the mixture of yeast and Lactobacillus rhamnosus YL-1 was applied to the fermented sausage model. The effect of the starter in the sausage model was investigated through physicochemical parameters, degree of fat oxidation, free fatty acid content, and though volatile flavor compound analysis, sensory evaluation and various indexes after storage were observed. The addition of yeast effectively reduced the POV and TBARS values of salami. The content of flavor compounds related to lipid oxidation, such as hexanal, heptanal, nonanal and (E) -2-decenal, were significantly lower in Debaryomyces. hansenii Y4-1 and Y12-3 groups. Meanwhile, the possible pathways of yeast metabolism of flavor substances related to lipid oxidation (mainly aldehydes) were discussed with the help of metagenomic techniques. According to the results of metagenomics, fatty acid degradation (ko00071) metabolic pathway was related to the degradation of aldehydes through aldehyde dehydrogenase, which was the potential key enzyme.